1997
DOI: 10.1021/ic970441s
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Transfer Kinetics and Thermodynamic Characterization of Copper(II/I) Complexes with Acyclic Tetrathiaethers in Aqueous Solution

Abstract: The kinetics of a series of Cu(II/I)−acyclic tetrathiaether complexes reacting with several oxidizing and reducing reagents have been examined in aqueous solution at 25 °C. This investigation has included a re-examination of CuII/I(Me2-2,3,2-S4) (Me2-2,3,2-S4 = 2,5,9,12-tetrathiatridecane = L12a), containing the ethylene−trimethylene−ethylene bridging sequence, plus three newly synthesized ligands containing an alternate bridging sequence of trimethylene−ethylene−trimethylene:  2,6,9,13-tetrathiatetradecane (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…In all three systems, the k 11(A) and k 11(B) values were similar to those observed with the Cu(II/I) systems involving the singly derivatized trans-cyclohexane and trans-cyclopentane derivatives. In a separate study, Dunn et al 141 also studied the electron-transfer kinetics of four comparable noncyclic tetrathiaether complexes with Cu(II/I) in which the central bridging moiety was ethylene, propylene, cis-cyclohexane, or trans-cyclohexane (listed at the beginning of Table 7). The k 11 values were surprisingly small (within the range of 10 -2 to 10 2 M -1 s -1 ) compared to the corresponding Cu II/I ( [14]aneS 4 ) values.…”
Section: Table 8 Electron Self-exchange Rate Constants For Pathways mentioning
confidence: 99%
See 1 more Smart Citation
“…In all three systems, the k 11(A) and k 11(B) values were similar to those observed with the Cu(II/I) systems involving the singly derivatized trans-cyclohexane and trans-cyclopentane derivatives. In a separate study, Dunn et al 141 also studied the electron-transfer kinetics of four comparable noncyclic tetrathiaether complexes with Cu(II/I) in which the central bridging moiety was ethylene, propylene, cis-cyclohexane, or trans-cyclohexane (listed at the beginning of Table 7). The k 11 values were surprisingly small (within the range of 10 -2 to 10 2 M -1 s -1 ) compared to the corresponding Cu II/I ( [14]aneS 4 ) values.…”
Section: Table 8 Electron Self-exchange Rate Constants For Pathways mentioning
confidence: 99%
“…Many blue copper sites exhibit redox potentials within the relatively narrow range of 0.2-0.4 V (vs SHE); 182 however, potentials as high as 1.0 V have been recorded. 183 The Cu(II/I) potentials of inorganic complexes in which the copper is coordinated to unsaturated nitrogen donors, to thiaether sulfur donor atoms, or to both are generally comparable to, and often exceed, these potentials, the highest value reported being 0.83 V. 141 Comparisons of the electron-transfer kinetic behavior of the cupredoxins to inorganic copper systems are somewhat problematic. The proteins normally function by having the substrate bind to a specific surface patch through electrostatic or hydrogenbonding interactions.…”
Section: Comparative Copper(ii/i) Blue Copper Protein Propertiesmentioning
confidence: 99%
“…[The ligand numbering scheme adopted is contiguous with numbers assigned to recently studied macrocyclic 14 and acyclic 61 tetrathiaether ligands. ]…”
Section: Introductionmentioning
confidence: 99%
“…For Cu II ([14]aneNS 3 -b), the measurements were carried out at pH 3.77 using a total ligand concentration of 28 µM while the total Cu() concentration was varied from 93 to 280 µM to yield a conditional stability constant value of K Cu II L Ј = (8.25 ± 0.09) × 10 3 M Ϫ1 . Our past studies with acyclic polythiaethers49 have amply demonstrated that the Cu()-polythiaether complexes are exceptionally weak in aqueous solution in the absence of complete coordination by a quadridentate macrocycle. Based on these prior observations, it is presumed that the protonated complex with[14]aneNS 3 , Cu II HL, is not a stable species under the conditions used in the current work.…”
mentioning
confidence: 99%